Peat Soil Stabilizer Using Plastic Waste - Nurul Syahira Izaty Abu Hassan; Dayang Zulaika Abang Hasbollah; Nordiana Mohd Muztaza; Yuliana Yuliana (Smart and Green Materials, 2024)
This paper shows the different in properties for peat soil and peat soil added with an increment of plastic waste (PET) Polyethylene Terephthalate type. The objective is to compare shear strength of the untreated and treated peat soil. There are four sample of soil use in this study. First, natural peat soil without additional of plastic bottle strips. Next, peat soil with an additional of 0.4% from the mass of soil, 0.5% plastic strip content and 0.6%of plastic bottle strips added to the peat soil. The stabilizer used are plastic bottles strip with 15mm x 15mm size with an increment of 0.4%,0.5% and 0.6%. the peat sample was retrieved from Mardi Pontian, Johor. The index properties of peat soil are obtained from the Atterberg Limit, Sieve Analysis and Loss of Ignition test. Standard Proctor compaction test result meet the objective of this research which is to determine the optimum value of Maximum Dry Density ad Optimum Moisture Content for the peat soil and the stabilized samples. The strength of treated and untreated samples has been determined by performing the Unconfined Compressive Strength (UCS) at 0 day and 28 days curing. From the laboratory test, the peat soil has 250% natural moisture content and 77% organic content. The specific gravity was in range of 1.48-1.8. The value for liquid limit is 230 and plastic limit is neglected as for peat and highly inorganic soils the Atterberg limit is not suitable to be performed on this type of soil. The MDD is increase and OMC results in reverse, but there are increment in strength of peat soil with the addition of 0.6% plastic bottles strips. Based on this study, the optimum value for MDD and OMC is at 0.4% of plastic strips content and 0.6% for shear strength.
Keywords: Geotechnical Engineering and Soil Stabilization; Grouting, Rheology, and Soil Mechanics; Landfill Environmental Impact Studies